THE HIGH K2O VOLCANISM OF NORTHWESTERN TIBET: GEOCHEMISTRY AND TECTONIC IMPLICATIONS - Arnaud N.O.; Vidal Ph.; Tapponnier P.; Matte Ph.; Deng W.M. (My University, 1992)
Cenozoic volcanic rocks sampled during the 1989 Sino-French Kunlun geotraverse have been analyzed to constrain the origin of widespread Tertiary to Neogene Tibetan basic magmatism. Samples ranging from phonotephrites to trachyandesites are high-K lavas (K/Na always greater than 1) which exhibit typical calc-alkaline characteristics, although they are highly enriched in mobile trace elements and REE (600 times chondrites for La). Isotopic compositions exhibit radiogenic Sr and Pb (87Sr/86Sr= 0.708; 208Pb/204Pb= 39–39.4; 207Pb/204Pb= 15.6–15.7; 206Pb/204Pb= 18.7) and unradiogenic Nd (143Nd/144Nd= 0.5123–0.5124). Constancy of Sr and Nd isotopic values contrasts with variations in Pb isotopes, and highlights the problem of crustal contamination. AFC and simple mixing models are compatible with isotopic variations but were probably buffered by elemental concentration in Sr and Nd, while Pb isotopic values for the most primitive magmas are probably uncontaminated. Isotopic features are therefore proposed to be representative of a mantle source in which heterogeneity could be highlighted in the Pb isotopic values. Such a source, highly enriched in trace elements and radiogenic Sr and Pb, is proposed to lay in the subcontinental mantle, isolated from the overall convection movements. The calc-alkaline characteristics can date from the succession of enrichment phases linked to the numerous subduction events that have affected this part of Asia, while the isotopic characteristics are proposed to be the result of the aging of the concomitant LILE enrichments.
Keywords: Cenozoic; Neogene; Cenozoic; Кайнозой::Неоген; Cenozoic::Neogene; Кайнозой